2022
DOI: 10.7591/cornell/9781501759574.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Roaming Free Like a Deer

Abstract: By exploring lived ecological experiences across seven Buddhist worlds from ancient India to the contemporary West, this book provides a comprehensive, critical, and innovative examination of the theories, practices, and real-world results of Buddhist environmental ethics. The book clarifies crucial contours of Buddhist vegetarianism or meat eating, nature mysticism, and cultural speculations about spirituality in nonhuman animals. Buddhist environmental ethics often are touted as useful weapons in the fight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…My thesis, which is in concert with that of Capper (2022), is difficult to demonstrate in this short essay because Buddhism is a diverse religious tradition and so are our possible interactions with the nonhuman world. Nevertheless, it may be useful to consider a story that involves the Chinese Buddhist master Zhuhong (1535-1615 CE).…”
Section: A Buddhist Ecological Practicementioning
confidence: 94%
See 3 more Smart Citations
“…My thesis, which is in concert with that of Capper (2022), is difficult to demonstrate in this short essay because Buddhism is a diverse religious tradition and so are our possible interactions with the nonhuman world. Nevertheless, it may be useful to consider a story that involves the Chinese Buddhist master Zhuhong (1535-1615 CE).…”
Section: A Buddhist Ecological Practicementioning
confidence: 94%
“…Examples like this one help to fuel the nature‐friendly reputations not just of Zhuhong but also of Buddhism itself, because this story is not isolated. My own research shows that numerous animal‐protecting stories can be found across Buddhist worlds including within the Buddha's life, Sri Lanka, Thailand, China, Japan, Tibet, and the contemporary West (Capper, 2022, pp. 1–11).…”
Section: A Buddhist Ecological Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Of course, the interests of humans, nonhuman animals, and ecosystems can (and often do) come into conflict. Capper (2022) mobilizes this conflict towards a critique of the eco-Buddhist project and writes that a Buddhist environmental ethic cannot "attend to the complexities of ecosystems with many preying individuals" (p. 217). Again, I have responded to this critique in detail elsewhere (Simonds 2023c), but it is worth restating some of my response here.…”
Section: Toward a Buddhist Ecological Care Ethicmentioning
confidence: 99%